Miskonsepsi Dalam Pembelajaran IPA - Kurniyatul Faizah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
In general, students who learn from several lessons already have some preceding knowledge related to the lessons they learn to learn. This also happens to students who are processing to study science. The students already have some experience and knowledge related to nature. Whether knowledge is true or false in theory. Having prior knowledge, it creates intuition and "student theory" about nature and the environment but is not always theoretically correct. In some countries, educators, especially science educators, are beginning to investigate the misconceptions about science knowledge preceded by students. It was found that there were some patterns in the misunderstanding. Apparently, most students consistently develop their own misunderstandings of science inadvertently and continue to follow the learning process of science. Misconceptions arise from everyday experiences and are difficult to rectify. If teachers teach science to students without considering the misconceptions of students before experiencing the learning process in school, then the teacher will not succeed in teaching the concept of science is right. Therefore, the need for consistency anticipation of misconceptions to make learning correction starts from the analysis of misconception into an alternative solution on how to overcome misunderstandings of science